Distributional Implications of Labor Market Reforms : Learning from Spain's Experience - Stepanyan, Ara (IMF Working Papers; Working Paper ;, 2020)
Spain's structural reforms, implemented around 2012, have arguably contributed to a faster and stronger economic recovery. In particular, there is strong evidence that the 2012 labor market reforms increased wage flexibility, which helped the Spanish economy to regain competitiveness and create jobs. But the impact of these labor reforms on income inequality and social inclusion has not been analyzed much. This paper aims to shed light on this issue by employing an econometric decomposition procedure combined with the synthetic control method. The results indicate that the 2012 labor reforms have helped improve employment and income equality outcomes with no substantial impact on the overall risk of poverty. Nevertheless, the reforms appear to have induced a deterioration of average hours worked, in-work poverty, and possibly also of involuntary part-time employment.